Integrating practice-based learning into formal education : stakeholder perspectives on the challenges of learning location cooperation (LLC) in Germany’s dual VET system - Schwede, Jana [Verfasser]; Heisler, Dietmar [Verfasser]; Harteis, Christian [Verfasser] (My University, 2025)
Germany’s dual Vocational Education and Training (VET) system has been criticized for insufficient cooperation among vocational schools, companies, and inter-company training centers, limiting its potential to effectively relate theory with practice. Despite the issue’s ongoing relevance, recent research on Learning Location Cooperation (LLC) remains scarce. This study addresses the existing research gap by examining contemporary LLC dynamics through the lens of key stakeholders. A total of 20 semi-structured interviews were conducted across interconnected learning locations, with each of the five targeted occupations represented by an apprentice, vocational teacher, trainer, and inter-company trainer. The study design enabled participants, connected through the apprentices’ learning journeys, to discuss LLC phenomena from their unique viewpoints, facilitating an in-depth exploration of cooperation strategies, relationships, conditions for success or failure, and desired improvements. Findings reveal both similarities and differences in perceptions, highlight diverse barriers, and provide actionable recommendations to strengthen LLC. These insights are crucial for refining Germany’s VET system and offer valuable lessons for international contexts, where integrating theory and practice is essential for developing a skilled and adaptable workforce. Overall, the study underscores the importance of fostering deeper cooperation among learning locations to ensure the effectiveness and sustainability of (vocational) education globally.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 2.4.1 Lernortkooperation; 370; Lernort Betrieb; Lernort Schule; Überbetriebliche Berufsbildungsstätte; Lernortkooperation; Interview